CREB Ameliorates Osteoarthritis Progression Through Regulating Chondrocytes Autophagy via the miR-373/METTL3/TFEB Axis - Zhang, Haibin; Li, Xilei; Li, Yusheng; Yang, Xucheng; Liao, Runzhi; Wang, Haoyi; Yang, Junxiao (Frontiers in Cell and Developmental Biology, 2022)
Osteoarthritis (OA) is a degenerative joint disease characterized by articular cartilage degradation. Dysregulated autophagy is a major cause of OA. However, the underlying mechanism is unclear. Here, we found that the expression of element-binding protein (CREB) was downregulated in both cartilage tissues of OA patients and mouse OA model. In tert-butyl hydroperoxide solution-treated chondrocytes, increased apoptosis and autophagic blockage were attenuated by CREB overexpression. Mechanically, MiR-373 directly targeted the 3′UTR of methyltransferase-like 3 (METTL3) and led to its downregulation. METTL3 epigenetically suppressed TFEB. The upregulation of miR-373 by CREB overexpression induced the release of TFEB from METTL3 and restored the autophagy activity of chondrocytes. Taken together, our study showed that CREB alleviates OA injury through regulating the expression of miR-373, which directly targeted METTL3, and finally relieved TFEB from METTL3-mediated epigenetic suppression. The CREB/miR-373/METTL3/TFEB axis may be used as a potential target for the treatment of OA.